2020
DOI: 10.3390/ijms21030888
|View full text |Cite
|
Sign up to set email alerts
|

Integrin Signaling in Glioma Pathogenesis: From Biology to Therapy

Abstract: Integrins are a large family of transmembrane adhesion receptors, which play a key role in interactions of a cell with the surrounding stroma. Integrins are comprised of non-covalently linked α and β chains, which form heterodimeric receptor complexes. The signals from integrin receptors are combined with those originating from growth factor receptors and participate in orchestrating morphological changes of cells, organization of the cytoskeleton, stimulation of cell proliferation and rescuing cells from prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 126 publications
4
74
0
Order By: Relevance
“…The EGFR-independent pathway may maintain stimulation of the PI3K-AKT signaling pathway. We and others previously reported an impact of integrin or JAK signaling in glioma intracellular signaling 55,56 , and other receptor tyrosine kinases 57-60 may be involved. Clark et al 57 demonstrated a compensatory activation of EGFRrelated family members (ERBB2 and ERBB3) that enabled glioma stem cell proliferation, suggesting that simultaneous blockade of multiple ERBB family members may be required for more efficacious GBM therapy.…”
Section: Discussionmentioning
confidence: 78%
“…The EGFR-independent pathway may maintain stimulation of the PI3K-AKT signaling pathway. We and others previously reported an impact of integrin or JAK signaling in glioma intracellular signaling 55,56 , and other receptor tyrosine kinases 57-60 may be involved. Clark et al 57 demonstrated a compensatory activation of EGFRrelated family members (ERBB2 and ERBB3) that enabled glioma stem cell proliferation, suggesting that simultaneous blockade of multiple ERBB family members may be required for more efficacious GBM therapy.…”
Section: Discussionmentioning
confidence: 78%
“…The hypoxia-induced SRC pathway entirely influences the process described above, finally resulting in fostered invasiveness. In fact, it primarily involves EGFR-vIII and integrin β3 interaction, the recruitment of αvβ3 integrin on GBM cell membranes and the creation of focal adhesion complexes by FAK activation [ 62 ]. Finally, the EGFRvIII / integrin β3 / FAK / SRC axis leads to the activation of the intracellular signaling pathway ERK1/2, MAPK, AKT, and STAT3, which determines the upregulation of MMP-2 and MMP-9, further promoting cell invasion [ 63 ].…”
Section: Hypoxic Regulation Of Src In Glioblastoma Development Andmentioning
confidence: 99%
“…In addition, it also augments TMZ-induced cytotoxicity in the rat glioma 9L cells subcutaneous mouse xenograft model. It has been reported that the expression levels of α5-integrin increase with glioma grade [ 108 , 109 , 110 , 111 ] and correlate with poor prognosis in high-grade glioma/GBM [ 108 ]. In particular, integrin α5β1 is expressed at significantly higher levels in mesenchymal GBM, which is the most aggressive subtype of GBM [ 110 ].…”
Section: Fibronectin-derived Peptide Fniii14mentioning
confidence: 99%
“…To date, many synthetic peptides based on FN bioactive sequences, which are mostly derived from the RGD sequence within the 10th FN type III domains or PHSRN sequence within the 9th FN type III domains, have been widely attempted in clinical studies as antitumor agents [ 109 ]. Cilengitide (EMD 121974), a cyclic RGD pentapeptide, is a selective integrin antagonist for αvβ3 and αvβ5, and acts in an antiangiogenic manner [ 109 ].…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%